Analisis Isi: Propaganda dalam Pemberitaan VOA-ISLAM Terhadap Kepemimpinan Jokowi - Adha Satrio Har Utomo, Noor; Yulianto, Muchammad (Interaksi Online, 2018)
Propaganda is a form of systematic communication which attempts to affect people’s worldview and behavior according to the interest of perpetrator of the propaganda. Mass media have a great role as medium for distributing the ideology of propaganda, and Voa-islam is no exception. As 2019 presidential election draw nearer, Voa-islam.com incessantly broadcasted series of news about Jokowi, who is an incumbent president, as the main object. This research aims to understand what form of propaganda is done by Voa-islam.com against Jokowi’s regime. The research uses descriptive quantitative approach and content analysis method with data analysis technic of frequency table by inputting data into tables categorically. Subject of the study is Jokowi. Paradigm in this research uses positivism and a theory called Agenda Setting theory. Result of this research shows that news from Voa-islam.com do not indicate a balance (cover both sides) characterized by the absence of informant from Jokowi’s side. The news from Voa-islam.com also tend to be biased and deploy hidden propaganda proven by the fact that most of the news do not mention Jokowi as the subject in them. From majority of the news made, Voa-islam.com uses propaganda technic called card stacking by taking groundless opinion from politician and public figure who are quoted from Twitter. Majority of moslem in Indonesia become the main target for Voa-islam.com news as mentioned in the redaction. Besides that, Voa-islam,com is one of the media which drives the mass emotional rising and leads to social movement in Internet such as symbolic aspiration of #2019GantiPresiden hashtag and several rallies by the people wearing clothes with #2019GantiPresiden on it as a part of opposition against Jokowi.